Appearance of Aortic Polymer-Filled Stent Grafts in CT Angiography - Mruk, Bartosz; Nowicki, Miroslaw; Zawadzki, Michal; Andziak, Piotr; Walecki, Jerzy; Sklinda, Katarzyna (Cardiology and Cardiovascular Medicine, 2019)
Nellix and Ovation stent grafts are new generation prostheses that utilize polymer technology to treat abdominal aortic aneurysms. The use of polymers in stent grafts aims to increase the number of eligible patients that can be treated by an endovascular approach and to reduce complications of unsuccessful exclusion of the aortic sac from systemic circulation. Knowledge of both normal structure and normal CT appearance of polymer stent grafts is critical for appropriate assessment of treatment efficacy in patients with abdominal aortic aneurysms and for detection of possible complications.